MICROBIAL POPULATIONS WHICH ACTIVELY INVOLVED AND OPTIMUM FERMENTATION CONDITION FACTORS IN PRODUCING \"TEA-CIDER\" - Kusnadi
Tea is an agricultural product containing beneficial substances, especially used for human health. The study of \"Tea-cider\" fermentation has been conducted using batch culture method. The purposes of the study were to observe microbial populations which were actively involved in the process of \"Tea-cider\" fermentation, to determine the optimum fermentation conditions, as well as to evaluate the inhibition effect of the product against pathogenic bacteria. The study was carried out in two steps. Firstly, the isolation of microorganisms from \"Tea-cider\"; secondly producing \"Tea-cider\" using mixed microbial culture isolated from \"Tea-cider\"and \"Tea-cider\" itself as inoculum (\'starter\'). Type and concentration of inoculumwere optimized for the fermentation process. Mixed of the pure of isolated microorganisms with variation of initial cell number at ratio B:K1:K2 = 1:1:1, 3:1:1 and 5:1:1, while the variation of starter were 5%,10% and 15% (v/v). Optimization in temperature, pH and sugar concentration at the variation 25°C, 28°C, 30°C and 35°C, pH of 4, 5 and 6, and sugar concentration 5%, 10% and 15% (w/v) respectively. The pH, acid concentration, reducing sugar concentration and alcohol concentration were analized at 48 hours interval during 14 days fermentation. The product was tested for antimicrobial effect using agar diffusion method and for organoleptic. The results showed that microbial populations which were actively involved in \"Teacider\" fermentation were yeasts Schizosaccharomyces pombe (Kl) and Brettanomyces sp. (K2), and a species of acetic acid bacteria Acetobacter xylinum (B). The optimum condition of \"Tea-cider\" fermentation were as follows, the ratio of B:K1:K2 optimum mixed culture inoculum at 5:1:1 and 10% (v/v) for the liquid starter. The incubation temperature was 30°C, the medium initial pH was 5 and the initial sugar concentaration was 10% (w/v).The \"Tea-cider\" product was able to inhibit the growth of some pathogenic bacteria such as Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coliand had a good preferred taste.